Adsorption Of Methylene Blue Dye From Liquid Phase By Carbon Nanotube-Infused Poly (VINYL) Alcohol Membrane - Ng, Zhi Heng (Universiti Sains Malaysia, 2018)
The PVA membrane and PVA incorporated with carbon nanotube (PVA/MWCNT) nanocomposite membrane were used as adsorbent to remove methylene blue from aqueous water. Several conditions of adsorption such as contact time, temperature and initial concentration of methylene blue were also investigated to determine the optimum condition of the adsorption. After 4 hours, there was no visible change in the removal of methylene blue (MB) dye on PVA membrane and PVA/MWCNT nanocomposite membrane surface. The adsorption capacity at equilibrium for PVA membrane was 0.102 mg/g while PVA/MWCNT nanocomposite membrane was 0.146 mg/g at 20℃. It was found that 4 hours is the optimized contact time for the adsorption process. The adsorption capacity of PVA membrane decreases while adsorption capacity of PVA/MWCNT nanocomposite membrane increases with increase in the initial concentration of MB dye from 1.0 mg/L to 4.0 mg/L. Besides, the adsorption capacity of PVA membrane decreases while adsorption capacity of PVA/MWCNT nanocomposite membrane increases with increase in the temperature from 25℃ to 40℃. On the other hand, the adsorption equilibrium data for PVA membrane was found to be well fitted with the type I of the Langmuir isotherm model while for PVA/MWCNT nanocomposite membrane it was found to be well fitted with both type I and type II of Langmuir isotherm model. Adsorption kinetics of MB dye removal using PVA membrane and PVA/MWCNT nanocomposite membrane was better described by pseudo-second order model.